Learning Model of Prophet Stories in the Islamic Education Curriculum to Instill the Value of Honesty in Children at Raudhatul Athfal - Mursal Aziz; Dedi Sahputra Napitupulu; Suciati Suciati (Bustanul Ulum Journal of Islamic Education, 2026)
This research is motivated by the importance of instilling honesty values ​​from an early age through the Islamic Education curriculum amidst the decline in children's moral character in everyday life. One effort is to implement a learning model of the stories of the prophets as an interesting character education medium and appropriate for early childhood development. This study aims to describe the learning model of the stories of the prophets in the Islamic Education curriculum to instill the value of honesty in children at RA Miftahul Ilmu. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Research informants consisted of the principal, teachers, parents, and students. The results showed that the learning model was implemented through storytelling methods, habituation, teacher role models, educational games, and direct interaction with children. The story of the Prophet Muhammad SAW as an example of honesty became the main material in the learning. The impact of this implementation model is seen in changes in children's behavior such as daring to tell the truth, admitting mistakes, and taking responsibility. This study concludes that the learning model of the stories of the prophets is effective in instilling honesty values ​​and shaping Islamic character in early childhood gradually and sustainably.